Proposing a Structural Model of Digital Leadership in the Banking Industry - Shateri, Tahereh; Amirkabiri, Alireza; Rabiei Mandejin, Mohammadreza (Digital Transformation and Administration Innovation, 2025)
The aim of the present study was to propose a structural model of digital leadership in the banking industry. This research employed a qualitative method and was applied in nature. The participants included experts consisting of university professors specializing in digitalization within the banking industry. Interviews were conducted with 17 individuals using purposive sampling until theoretical saturation was achieved. The research instrument was semi-structured interviews. The validity of the interviews was examined through face validity, and their reliability was assessed using inter-coder agreement. Data analysis was performed using coding techniques. Additionally, to identify the causal relationships among the components of digital leadership in the banking industry, the Structural Interpretive Modeling (SEM) method was used. The results revealed that digital leadership in the banking industry consists of 13 main components organized into four levels. At the first level, components such as collaborative and digital networking leadership, agile and adaptive digital leadership, digital leadership for customer experience improvement, and leadership in digital change management were identified as key and independent factors in digital processes. These components have high leverage and can rapidly generate significant changes within the organization. At the second level, components such as innovation and change leadership, cultural and human-centered leadership, and data-driven leadership were identified. The third level included leadership in the areas of cybersecurity and privacy. The fourth level was comprised of strategic digital leadership, which showed low influence and high dependency on other components. It can be concluded that the structural model of digital leadership in the banking industry could have significant implications for the country's banking system. Emphasis on digital leadership should be placed on the first level, which includes the key and independent factors in digital leadership.